Application status and research progress of targeted therapy drugs for hormone receptor-positive breast cancer - Han Luo; Yue Sun; Tiefeng Xu; Tiefeng Xu (Frontiers in Medicine, 2025)
Breast cancer (BC) is the most common malignant tumor in women and the leading cause of cancer-related deaths in women. As one of the most common subtypes of breast cancer, patients with hormone receptor-positive (HR+) breast cancer usually experience disease progression over an extended period of time, triggering the search for therapeutic strategies other than endocrine therapy. In recent years, continuous research on various targets has led to dramatic changes in the treatment of hormone receptor-positive breast cancer patients, resulting in prolonged clinical survival. With the redefinition of human epidermal growth factor-2 (HER2) expression, more precise and individualized treatment is possible. This review comprehensively reviews targeted therapies and critical clinical trials for HR+ breast cancer and tracks the latest advances. It also provides valuable insights into the future direction of targeted therapies.